Data for "Patterns of enzyme activities and nutrient availability within biocrusts under increasing aridity in Negev desert" - Drahorad, Sylvie; Heinze, Stefanie; Justus Liebig University Giessen (My University, 2022)
This dataset contains the raw data of the open access article "Patterns of enzyme activities and nutrient availability within biocrusts under increasing aridity in Negev desert". All raw data is listed in two excel sheets. Excel sheet one contains the soil related data provided by the first author at the Justus-Liebig-University Gießen, excel sheet two contains the enzyme data provided by the last author at the Ruhr-Universität Bochum. The soil data presents 5 replicates of biocrust samples at two study sites (S1-S5 and N1-N5). Three samples of each site were choosen for enzyme measurements, each provided as four pseudoreplicates. The methods of data production can be found in the original open access published article "Patterns of enzyme activities and nutrient availability within biocrusts under increasing aridity in Negev desert".
Keywords: soil science; ddc:550; ddc:570